In-water and on-land swimmers` symmetry and force production - Carvalho, D. D.; Soares, S.; Zacca, R.; Marinho, D. A.; Silva, A. J.; Pyne, D. B.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Environmental Research and Public Health, 2019)
Although performance and biomechanical evaluations are becoming more swimming-specific, dryland testing permits monitoring of a larger number of performance-related variables. However, as the degree of comparability of measurements conducted in-water and on land conditions is unclear, we aimed to assess the differences between force production in these two different conditions. Twelve elite swimmers performed a 30 s tethered swimming test and four isokinetic tests (shoulder and knee extension at 90 and 300°/s) to assess peak force, peak and average torque, and power symmetry index. We observed contralateral symmetry in all the tests performed, e.g., for 30 s tethered swimming and peak torque shoulder extension at 90°/s: 178 ± 50 vs. 183 ± 56 N (p = 0.38) and 95 ± 37 vs. 94 ± 35 N × m (p = 0.52). Moderate to very large direct relationships were evident between dryland testing and swimming force production (r = 0.62 to 0.96; p < 0.05). Swimmers maintained similar symmetry index values independently of the testing conditions (r = -0.06 to -0.41 and 0.04 to 0.44; p = 0.18-0.88). Asymmetries in water seems to be more related to technical constraints than muscular imbalances, but swimmers that displayed higher propulsive forces were the ones with greater force values on land. Thus, tethered swimming and isokinetic evaluations are useful for assessing muscular imbalances regarding propulsive force production and technical asymmetries.